2015
DOI: 10.5371/hp.2015.27.3.135
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term Results of Revision Total Hip Arthroplasty Using Modular Cementless Femoral Stems

Abstract: PurposeThe purpose of this study was to evaluate the clinical and radiological results of revision total hip arthroplasty using modular distal fixation stems for proximal femoral deficiency.Materials and MethodsForty-five patients (47 hips) were analyzed more than 24 months after revision total hip arthroplasty that used modular distal fixation stems and was performed between 2006 and 2012. There were proximal femoral defects in all cases. Preoperative femoral defect classification revealed Paprosky type II in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…In spite of satisfactory clinical results consistent with previous studies [7,28,32,33], we identi ed some complications. Instability was reported in 6% of the cases.…”
Section: Discussionsupporting
confidence: 84%
“…In spite of satisfactory clinical results consistent with previous studies [7,28,32,33], we identi ed some complications. Instability was reported in 6% of the cases.…”
Section: Discussionsupporting
confidence: 84%
“…Fink et al (11) reported all-cause implant survival at 7.5 years to be 91.4% (95% CI, 86.2%-96.6%). In their cohort of 45 patients (47 hips), Jang et al (24) revised 5 hips for deep infection and 2 hips for dislocation. The 8-year survival rate, with revision for any reason as an event of interest, was 86%.…”
Section: Discussionmentioning
confidence: 99%
“…Huddleston et al (21) reported lower revision rate for modular stems, whilst Mertl et al (10) found a higher rate of failure for MNFS. However, compared to monolithic stems, modular implants greatly simplify strategies for revision THA and following failures of revision as the modular neck can be removed, facilitating exposure and replaced easily to adapt offset, limb length and NSA while leaving the intramedullary part of the stem stably fixed within the femur, which has relatively good bone quality at mid-term followup (42,(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%